The Impact Of Job Characteristics, Training Opportunities, And Leadership Styles On Turnover Intention With Job Satisfaction As Mediation - Enggar Galih Mitayani Purwanto; Rhian Indradewa (Cakrawala Repositori IMWI, 2023)
Turnover intention is an early indicator of a person's likelihood to leave their job. The tendency of employees to move can cause several negative impacts including company costs for recruiting and training new employees, lower productivity, instability in terms of overall company performance and reduced satisfaction among remaining employees. The purpose of this study is to determine the effect of job characteristics, training opportunities, leadership style on turnover intention with job satisfaction as mediation. Research data collection was carried out by questionnaires distributed during the survey period in February - March 2023 to 195 employees. The research data were processed and analyzed using the Structural Equation Model Partial Least Square (SEM-PLS). The results showed that job characteristics and training opportunities have a direct negative effect on turnover intention or with job satisfaction as mediation. Meanwhile, leadership style has no direct effect on turnover intention or job satisfaction as mediation. The managerial implication of this research for companies is to improve job characteristics and training opportunities to increase job satisfaction so as to reduce turnover intention.